A systems perspective on financial systems - Forrest, Jeffrey Yi-Lin, 1959- (Communications in cybernetics, systems science and engineering ;, 2014)
This book is devoted to a systems-theoretical presentation of the main results of money and financial institutions by using the systemic yoyo model and relevant analytical tools. The author presents the main concepts and results of the subject matter in the language of systems science, which has in the past century brought forward revolutionary applications of systems research in various areas of the traditional disciplines. Because of the brand new logic of reasoning applied in this volume, some of the unsettled problems in the area of money and banking are addressed beautifully so that th.